Zinc deficiency effect on clinical features of Coronavirus Disease 2019 patients: A scoping review - Moch Ikhsan Juliansyah; Lisa Adhia Garina; Mirasari Putri (Acta Biochimica Indonesiana, 2023)
COVID-19 was declared a pandemic in March 2020. Various therapeutic guidelines have been established for treating COVID-19, such as anti-inflammatory, antiviral therapies, and zinc supplementation. Zinc deficiency is thought to worsen the condition of patients with COVID-19 infection. However, the effect of zinc deficiency on COVID-19 patients has not been widely reported. In this scoping review, we aim to explore the impact of zinc deficiency on the clinical features of COVID-19 patients. A comprehensive search was conducted across the databases, including PubMed, ScienceDirect, Springer Link, ProQuest, and Google Scholar, using the keywords “Zinc” AND “(COVID-19 or SARS-CoV-2)”. A total of 2,458 articles published between 2019 and 2020 were screened following the PRISMA guidelines and subjected to critical appraisal. Three articles were included, focusing on the effect of zinc deficiency on the clinical features of COVID-19 patients. As of 2022, two articles reported worsening symptoms, one described an increased hospitalization duration, and one reported worsening treatment outcomes in the zinc deficiency group. This review concludes that zinc deficiency worsens symptoms, increases the duration of hospitalization, and leads to worse outcomes in COVID-19 patients.